The ATLAS level-1 calorimeter trigger: preprocessor implementation and performance - Åsman, Barbro; Achenbach, Ralf; Anders, Gabriel; Andrei, George Victor; Davygora, Yuriy; Dorn, Markus; Föhlisch, Florian; Hanke, Paul; Djuvsland, Julia Isabell; Keller, Michael; Khomich, Andrei; Kluge, Eike-Erik; et al. (Journal of Instrumentation, 2012)
The PreProcessor system of the ATLAS Level-1 Calorimeter Trigger (L1Calo) receives about 7200 analogue signals from the electromagnetic and hadronic components of the calorimetric detector system. Lateral division results in cells which are pre-summed to so-called Trigger Towers of size 0.1 × 0.1 along azimuth ( ##IMG## [http://ej.iop.org/icons/Entities/phi.gif] phi ) and pseudorapidity (η). The received calorimeter signals represent deposits of transverse energy. The system consists of 124 individual PreProcessor modules that digitise the input signals for each LHC collision, and provide energy and timing information to the digital processors of the L1Calo system, which identify physics objects forming much of the basis for the full ATLAS first level trigger decision. This paper describes the architecture of the PreProcessor, its hardware realisation, functionality, and performance.